Anti-Inflammatory Activity and Mechanism of Hydrostatin-SN1 From Hydrophis cyanocinctus in Interleukin-10 Knockout Mice - Zhang, Chuan; Guo, Shanshan; Wang, Junjie; Li, An; Sun, Kuo; Qiu, Lei; Li, Jianzhong; Wang, Sheng; Ma, Xingyuan; Lu, Yiming (Frontiers in Pharmacology, 2020)
Biopeptides derived from marine species have garnered significant research interest owing to their anti-inflammatory, antibacterial, and anticancer activities. In our previous study, Hydrostatin-SN1, a bioactive peptide extracted from the Hydrophis cyanocinctus venom gland T7 phage display library, demonstrated anti-inflammatory activity in a dextran sulfate sodium-induced murine colitis model. In this study, we investigated the anti-inflammatory activity and the underlying mechanism of Hydrostatin-SN1 in lipopolysaccharide (LPS)-induced bone marrow-derived macrophage (BMDM) cells and interleukin (IL)-10 knockout mice. The results showed that Hydrostatin-SN1 inhibited phosphorylation of JNK, ERK1/2, and p38 and decreased the mRNA expression of tumor necrosis factor-α (TNF-α), IL-6, and IL-1β in LPS-stimulated BMDM cells in a dose-dependent manner. In LPS-induced acute shock model, a significant higher survival rate of Hydrostatin-SN1-treated mice was observed. Furthermore, Hydrostatin-SN1 reduced body weight loss, decreased disease activity index, reduced spleen index, prevented histological injury, and inhibited the expression of IL-β and phosphorylation of JNK, ERK1/2, and p38 in the colon tissue of IL-10 knockout mice. Additionally, the positive expression rate of TNF-α in mice colon was decreased. Overall, our results suggest that Hydrostatin-SN1 has significant anti-inflammatory effects, both in vitro and in vivo.